Allostatic Load in Gambel’s White Crowned Sparrow, Zonotrichia leucophrys gambelii: Relationships With Glucocorticoids - Word, Karen R.; Austin, Suzanne H.; Wingfield, John C. (Frontiers in Ecology and Evolution, 2022)
Regulation of energetic expenditure in a changing environment, considered here as allostatic load, is central to organism-environment interactions. The value of responses that modify behavior or physiology in coping strategies is often measured in terms of energetic benefits. In this study, the total energetic cost incurred by Gambel’s white-crowned sparrows, Zonotrichia leucophrys gambelii, was assessed using heart-rate transmitters. The use of heart rate was validated as a proxy for metabolic rate via flow-through respirometry. Applying heart rate as an indicator of allostatic load, we confirmed that ambient temperature under wintering conditions influences allostatic load. However, baseline corticosterone, proposed to mediate physiological responses to variation in allostatic load, does not appear to vary with heart rate or temperature in captivity, or with temperature under ambient conditions in the field. The relationship between allostatic load and plasma corticosterone levels was also investigated by manipulating feeding effort for captive Gambel’s white-crowned sparrows using a sand-excavation challenge that approximated a type of foraging work that these birds normally perform in the wild. This experiment was designed to test the hypothesis that experimentally increased allostatic load induces elevation in baseline corticosteroids. We did not find support for this hypothesis. We suggest that the adrenocortical response to increased allostatic load may be limited to overload or environmental conditions that meaningfully threaten energy imbalance, indicating new targets for further research.